Controlled Cities - G. Cortés, José Miguel (Re-visiones, 2024)
This text aims to analyze the relation between the organization and the structuring of city spaces by architecture and urban planning, and the homogenization of bodies and social exclusion existing in cities. A situation that acquires special traits thanks to the spread of a cyber technology that deeply modifies the most common spatio-temporal relations. Against this background, it is highly significant to find the creation of dissident geographies by some artists and architects who propose more plural and ambiguous spaces.